Analysis of the Influence of Discipline and Job Satisfaction on Employee Achievement Improvement in the Digital Era - Kusumah, Anuraga; Suharti, Titing; Prasetia, Angga; Muzaky , Rizqi (Universitas Ibn Khladun Bogor, 2025)
This study aims to analyze the influence of discipline and job satisfaction on employee work performance. The research method used is a quantitative approach with multiple linear regression analysis techniques. Data was obtained through the distribution of questionnaires to 53 respondents who were active employees. The results of the validity and reliability test showed that the research instrument was feasible to use. The results of the descriptive analysis showed that work discipline had an average score of 3.62, job satisfaction of 3.87, and work achievement of 4.15, which were generally included in the good category. Statistical tests showed that simultaneously discipline and job satisfaction had a significant effect on work performance, with a multiple correlation coefficient (R) of 0.753 and a determination coefficient (R²) of 0.568. This shows that 56.8% of the variation in work performance can be explained by both independent variables, while the rest is influenced by other factors. These findings reinforce the importance of managing discipline and job satisfaction simultaneously to improve employee performance. This research provides practical implications for management in designing data-based human resource policies.